Colloquium: Beyond the Gift: the Economy of Greek ‘Colonisation: Introduction - Donnellan, Lieve (Journal of Greek Archaeology, 2020)
Interregional networks are increasingly being scrutinised as the drive behind local change in the Late Bronze/Early Iron Age and Early Archaic world. Attempting to replace the dominant ‘colonisation’ paradigm, steeped in an outdated imperial vocabulary and anachronistic implications recently laid bare by postcolonial theory, critical analysis has attempted to stress the varied encounters and flexible responses they incited throughout the Mediterranean. Rather than static systems or strictly delineated cultural blocks of ‘Greeks’, ‘Phoenicians’ or ‘Etruscans’, meeting, with cultural transfers taking place in a single direction, from a centre to a periphery, attention is now paid to the direction and, importantly, the nature of exchanges. The increased appreciation of the multi-scalar effect of networks has also led to a higher sensitivity to the micro and meso levels in which interregional networks were embedded. It is in the daily life and interactions in which social realities are produced that we need to seek the reception, success and transformations brought about by the mobility of technologies, objects and people.